2019
DOI: 10.1111/jicd.12388
|View full text |Cite
|
Sign up to set email alerts
|

Influence of psychological stress exposure on orthodontic therapy: A comprehensive review

Abstract: Psychological stress exposure (PSE) is a major risk factor for neurological disorders, such as bipolar disorder, depression, and schizophrenia; 1 however, it is also associated with the etiopathogenesis of oral inflammatory conditions, including gingivitis, periodontitis, and aphthous stomatitis. 2 One explanation for this is that PSE increases blood cortisol levels, thereby compromising immune system activity and reducing monocyte and T-lymphocyte counts. 3,4 Moreover, PSE compromises wound healing by reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Moreover, an underprivileged SES is a well-known risk factor of obesity (Keaver et al, 2019). Studies (Harrist et al, 2016; Janssen et al, 2004) have shown that overweight children are at higher risk for bullying and teasing, and have more psychological problems than normal-weight peers (Rankin et al, 2016), which may negatively influence treatment compliance and outcome of OT (Al-Shammery et al, 2019). It has also been reported that nicotine (Michelogiannakis et al, 2018b) and alcohol consumption (Schroder et al, 2018) alter bone remodelling and may jeopardise the outcome of OT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an underprivileged SES is a well-known risk factor of obesity (Keaver et al, 2019). Studies (Harrist et al, 2016; Janssen et al, 2004) have shown that overweight children are at higher risk for bullying and teasing, and have more psychological problems than normal-weight peers (Rankin et al, 2016), which may negatively influence treatment compliance and outcome of OT (Al-Shammery et al, 2019). It has also been reported that nicotine (Michelogiannakis et al, 2018b) and alcohol consumption (Schroder et al, 2018) alter bone remodelling and may jeopardise the outcome of OT.…”
Section: Discussionmentioning
confidence: 99%
“…Local factors that have been reported to influence OTM encompass age, gender, root morphology and nicotine intake (Chisari et al, 2014; Giannopoulou et al, 2016; Michelogiannakis et al, 2018b; Naveh and Weiner, 2015). Moreover, use of medications such as corticosteroids and systemic conditions including psychological stress and diabetes mellitus may also affect OTM (Al-Shammery et al, 2019; Michelogiannakis et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Moreover, habits, such as tobacco smoking, and systemic diseases, including obesity, chronic hyperglycemia, and psychologic disorders, negatively influence orthodontically induced tooth movement in vulnerable populations. [30][31][32][33] Furthermore, use of medications, such as corticosteroids, non-steroidal anti-inflammatory drugs, and bisphosphonates, have been shown to compromise orthodontic tooth movement. [34][35][36] Under such circumstances, in-person patient evaluation prior to and during orthodontic therapy may facilitate identification and management of the potential risk factors, and may also help modify the traditional orthodontic treatment plan accordingly.…”
Section: Case Selection Diagnosis and Treatment Planningmentioning
confidence: 99%
“…66,70 Ancak konvansiyonel sabit tedavi gören hastaların, psikolojik karakterini belirlemeye yönelik yapılan araştırmaların az olduğu görülmüştür. 11,65,71 Kiyak ve arkadaşları, 67 konvansiyonel ortodontik tedavi gören hastalar üzerinde yapmış oldukları çalışmada, ortodontik tedavinin zamanla moral skorlarında önemli değişiklikler meydana getirdiğini ve stresli bir olay haline dönüştüğünü bildirmişlerdir. Ancak tedavinin tamamlanması ile tüm emosyonel değerlerin normal seviyeye döndüğü rapor edilmiştir.…”
Section: Tartiġmaunclassified